Prioritizing Power demand response for Hydrogen PEMFC-Electric Vehicles using Hybrid Energy Storage - Jawadi Samir; Ben Slama Sami; Cherif Adnane (International Journal of Electrical and Computer Engineering (IJECE), 2017)
PEMFC powered Hybrid vehicle system is one of an interesting issue for the industry due to its high performances. The PEMFC cannot certainly ensure a sustained required energy in some scenarios. To solve this problem related to PEMFC transient response, a Hybrid Electrical Storage System (HES) is a potential candidate for a solution. The proposed Hybrid Storage system is comprised of the battery (BT) and a Super-Capacitor (SC) components. These components are included to control the hydrogen variations and the fast peak powers scenarios respectively. The SC is used to control PEMFC and the BT slow dynamics at the same times. An accurate Multi-Ways Energy Management System (MW-EMS) is proposed which aims to cooperate with the system components through SC/BT state of charge and a flux calculation. The simulation results are discussed and assessed using  MATLAB/ Simulink.